Retail Analytics Ecosystem: Predictive Modeling Across Store Operations, Supply Chain, and Marketing Investment - Kandakumar, Karthik Kumar (IPHO-Journal of Advance Research in Science And Engineering, 2025)
This article explores the transformative potential of predictive analytics in retail environments, examining cross-functional applications across store operations, supply chain management, and marketing. The article addresses a significant gap in understanding integrated analytical approaches by presenting empirical evidence from implementation cases, including store health monitoring systems across retail locations, centralized trailer intelligence for supply chain optimization, and advanced marketing ROI enhancement methodologies. The article on operationalization strategies, risk detection algorithms, predictive modeling techniques, and implementation frameworks demonstrates how retailers can leverage analytics to drive proactive decision-making, improve operational efficiency, and optimize resource allocation. The findings highlight the synergistic benefits of a coordinated analytics strategy that transcends traditional organizational boundaries, providing a comprehensive framework for retailers seeking to enhance performance through data-driven approaches